Towards a UTAUT-based Model for the Intention to use Solar Water Heaters by Libyan households - Saleh, Ahmed Mohamed; Haris, Asmaddy Bin; Ahmad, Nursilah Bint (International Journal of Energy Economics and Policy, 2013)
Among the most fundamental features to ensure the success of a new technology introduction is citizen acceptance. Based on a unified model, called the Unified Theory of Adoption and Use of Technology (UTAUT), this paper provides new insights into predicting adoption and identifying of the factors that may prompt people to accept and use of Solar Water Heaters as a concrete step toward using Renewable Energy Resources, and offer guidelines for energy saving for the Libyan government and that will contribute to the economy of the country. Keywords: Solar Water Heaters; Technology Acceptance; the Unified Theory of Adoption and Use of Technology (UTAUT); Libyan Household JEL Classifications: D10; Q20; Q42; Q48